2002
DOI: 10.1002/1521-3951(200212)234:3<915::aid-pssb915>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of RF-MBE Grown AlGaAsN

Abstract: PACS: 78.30.Fs; 78.66.Fd; 81.15.Hi Raman scattering and infrared absorption properties of RF-MBE grown AlGaAsN layers have been reported in order to investigate the microscopic lattice structures related with the nitrogen incorporation. Several new Raman modes of the Al-N bonds have been observed at 449, 500, and 650 cm --1 in the Raman spectra of AlGaAsN (Al: 18-100%, N: 2%) instead of the mode of Ga-N bonds. The results strongly indicated that most of the N atoms form the Al-N bonds in the AlGaAsN layers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
7
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
3
7
0
Order By: Relevance
“…We have also already pointed out that temperature dependence of Hall electron mobility may be influenced by N spatial distributions in GaAsN and InGaAsN [2]. On the other hand, for AlGaAsN, several research groups have reported that N atoms are incorporated randomly because of preferential bond formation of Al-N bonds due to their large bond-formation energy [3,4]. Therefore, it is very interesting to investigate the temperature dependence of the Hall mobility in the AlGaAsN in order to reveal some correlation between the electrical properties and the N spatial distributions.…”
Section: Introductionmentioning
confidence: 99%
“…We have also already pointed out that temperature dependence of Hall electron mobility may be influenced by N spatial distributions in GaAsN and InGaAsN [2]. On the other hand, for AlGaAsN, several research groups have reported that N atoms are incorporated randomly because of preferential bond formation of Al-N bonds due to their large bond-formation energy [3,4]. Therefore, it is very interesting to investigate the temperature dependence of the Hall mobility in the AlGaAsN in order to reveal some correlation between the electrical properties and the N spatial distributions.…”
Section: Introductionmentioning
confidence: 99%
“…To comprehend the observed IR and Raman spectroscopy data [9][10][11][12][13][14][15][16][17][18][19] of LVMs in quaternary Ga 1−x In x ͑Al x ͒N y As 1−y alloys ͑for 0 Ͻ x Ͻ 1 with y ϳ 0.03͒ one can select five isolated elementary tetrahedrons ͑microclusters͒ related to the incorporation of nitrogen ͓see Fig. 2: viz, NIn p ͑Al p ͒Ga 4−p with p = 0, 1, 2, 3, and 4: NGa 4 ͑T d ͒, NIn 1 ͑Al 1 ͒Ga 3 ͑C 3v ͒, NIn 2 ͑Al 2 ͒Ga 2 ͑C 2v ͒, NIn 3 ͑Al 3 ͒Ga 1 ͑C 3v ͒, and NIn 4 ͑Al 4 ͒͑T d ͔͒.…”
Section: Microclustersmentioning
confidence: 99%
“…As compared to Ga 1−x In x N y As 1−y very few attempts have been made for evaluating the microscopic lattice structures related to the N incorporation in Ga 1−x Al x N y As 1−y alloys [14][15][16][17][18] Yamamoto and co-workers 14,15 reported optical properties of Ga 1−x Al x N y As 1−y / GaAs ͑with 0.18Ͻ x ഛ 1 and y ϳ 0.02͒ by using Raman and IR spectroscopies while Köhler and co-workers [16][17][18] have studied the vibrational features using Raman scattering on Ga 1−x Al x As 1−y N y / GaAs layers ͑with x ഛ 0.05 and y ഛ 0.04͒ grown by solid source MBE. Although several Raman modes ͑ϳ449, 500, and 650 cm −1 ͒ of the Al-N bonds have been observed 14,15 the knowledge of an isolated N As local mode in AlAs is, however, still sketchy.…”
Section: B Ga 1−x Al X N Y As 1−y Alloysmentioning
confidence: 99%
See 2 more Smart Citations